Putusan Hakim Pengadilan Negeri Surakarta terhadap Perkawinan Beda Agama yang Legal Secara Hukum Negara - Muhammad Husni Abdulah Pakarti (Mutawasith: Jurnal Hukum Islam, 2022)
This article discusses intermarriage which has been an endless controversy even though most religions have banned the practice of marriage. Section 35a of Population Act No. 23 of 2006 became the basis for heterosexual marriage agreements, after being rejected by the civil status registry due to marital obstacles. To determine a trial, the judge studies the law according to his knowledge and experience. At Decree No. 454 / Pdt.P / 2018 / PNSKt. For example, judges allow marriage between parents, but on the other hand, many decisions are reversed, so researchers are interested in this issue. The research method used is qualitative research (library study) with sociological and normative legal approach. The results show that marriages between married couples can be prosecuted as long as they get the permission of the district court by filing an application with rebuttal evidence as evidence, then can be registered in the military. team. But there are a few barriers, namely the emergence of legal uncertainty that make post-marital decisions so diverse and impactful that married couples think twice. thousands of times about marriages according to different religions.